Promotive effects of hyperthermia on the inhibition of DNA synthesis in Ehrlich ascites tumor cells by eicosapentaenoic and docosahexaenoic acids - Tanaka, H.; Kageyama, K.; Kimura, M.; Iwamoto, S.I.; Ueno, Y.; Asagi, K.; Asada, R.; Miwa, N. (Experimental Oncology, 2006)
Aim: To evaluate inhibitory effects of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) on DNA synthesis in combination with hyperthermia in vitro. Methods: A suspension of Ehrlich ascites tumor cells (EAT) was mixed with DHA or EPA in a glass tube, heated at 37 °C, 40 °C, or 42 °C for 1 h in a water bath, and cultured at 37 °C for 19 or 96 h. DNA synthesis was assayed by monitoring of the incorporation of [3H]-thymidine into the acid-insoluble fraction. DHA or EPA incorporated into EAT cells was extracted and measured by thin-layer chromatography and gas-liquid chromatography. Results: The inhibition of DNA synthesis by EPA or DHA increased markedly upon the treatment at 42 °C and 40 °C compared to that at 37 °C. At 37 °C, inhibitory action of EPA was more potent than that of DHA at low concentrations (at 50 µM — DNA synthesis level: EPA, 63.1%; DHA, 87.9%), whereas inhibitory action of DHA was higher at 150 µM (16.7%, 4.4%, ibid.). The effect of DHA compared to EPA was more marked at 40 °C (29.0%, 19.2% at 100 µM) or 42 °C (19.7%, 10.6% at 100 µM). Evaluation of DNA synthesis rate in the cells treated for 1 h by EPA or DHA with the next culturing of EAT cells for 19 h resulted in the enhanced inhibitory activity of EPA even at concentrations as low as 50 µM at either 37 °C (0.5%, 11.3%) or 42 °C (0.6%, 4.5%), which in these conditions was higher than that of DHA. At the same time the rate of incorporation of EPA in EAT cells at 37 °C or 42 °C was lower than that of DHA. Conclusion: Administration of DHA or EPA in vitro significantly inhibit DNA synthesis, and such effect is enhanced by combination of PUFAs with hyperthermia. Цель: исследовать ингибирующее воздействие эйкозопентаеновой кислоты (EPA) и докозагексаеновой кислоты (DHA)
на синтез ДНК в комбинации с гипертермией в модели in vitro. Методы: суспензию клеток асцитной карциномы Эрлиха
(EAT) смешивали с DHA или EPA в стеклянной пробирке, инкубировали в течение 1 ч при 37 °C, 40 °C или 42 °C
в водяной бане и культивировали при 37 °C 19 или 96 ч. Синтез ДНК оценивали по уровню включения [3
H]-тимидина.
DHA или EPA, включившиеся в клетки EAT cells, экстрагировали, а их количество определяли методами тонкослойной
и газожидкостной хроматографии. Результаты: степень ингибирования синтеза ДНК при действии EPA или DHA
значительно возрастала при обработке клеток при 42 °C в сравнении с таковым при 37 °C. При 37 °C ингибирующее
действие EPA было более выраженным, чем таковое DHA в низких концентрациях (при концентрации 50 μM — 63,1
против 87,9%), а DHA — более сильным при концентрации 150 μM (16,7 vs 4,4%). Эффект DHA в сравнении с EPA
был более выраженным при 40 °C (29,0 vs 19,2% при концентрации 100 μM) или 42 °C (19,7 vs 10,6% при концентрации
100 μM). При обработке клеток EPA или DHA с последующим культивированием в течение 96 ч наблюдалось
усиление ингибирующего воздействия EPA даже при концентрации 50 μM как при 37 °C (0,5 vs 11,3%), так и при
42 °C (0,6 vs 4,5%), что в таких условиях было значительнее, чем у DHA. В то же время степень включения EPA в
клетки EAT при 37 °C или 42 °C была ниже, чем таковая DHA. Выводы: введение DHA или EPA in vitro значительно
ингибирует синтез ДНК, и этот эффект усиливается на фоне комбинированного применения кислот и гипертермии.